Hinduism before reform - Hatcher, Brian A. (Harvard University Press, 2020)
How did Hindu reformers make the religion modern? Brian Hatcher argues that this is the wrong question to ask. Exploring two nineteenth-century Hindu movements, the Brahmo Samaj and the Swaminarayan Sampraday, he challenges the notion of religious reform